(untitled) (UNED Research Journal, 2026)
Introduction: Urban growth has reduced vegetation cover and biodiversity, affecting environmental quality and human well-being. Urban green areas provide regulating ecosystem services, including carbon capture and storage; however, data from the tropics—key regions for global biodiversity—remain scarce. Objective: To evaluate, for the first time, carbon stocks and the phytosanitary condition of trees in public urban green areas of the Cubujuquí Interurban Biological Corridor, Heredia, Costa Rica. Methods: We assessed carbon storage and phytosanitary status in 1 256 individuals representing 117 species. Results: The canton of Alajuela showed the highest carbon storage (27,625Mg C; 101,301Mg CO₂), whereas Flores and San Pablo recorded the lowest values. In total, the sample of 45 parks within the corridor stores 74,784Mg C, equivalent to 261,876Mg CO₂. Conclusion: Public green areas within the corridor function as urban carbon sinks with good phytosanitary conditions, contributing to tropical biodiversity conservation and climate change mitigation.